Pengaruh Bauran Pemasaran 7p Terhadap Keputusan Pembelian Konsumen Rumah Pandora 88 Jember - Rizky Pramana Putra; Haifa; Ahmad Sauqi3 (CV. ITTC INDONESIA, 2025)
This study aims to test the effect of Product Quality, Service Quality, Price, Promotion, Location, and Store Atmosphere on Purchasing Decisions at Pandora 88 Jember Restaurant. The data for this study were obtained from distributing questionnaires to research objects with purposive sampling techniques. This type of research is Quantitative. Respondents were seventy respondents. Data analysis in this study used Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, multiple linear regression analysis test, Determination Test (R2), t Test, F Test. The results of this study indicate that product quality and price variables have a significant effect on purchasing decisions, while Service Quality, Promotion, Location and Store Atmosphere do not have a significant effect on purchasing decisions. The value (Adjusted R2) is twenty seven point one percent